Financial condition and bankruptcy likelihood in aviation on the example of the Aeroflot company - Nargis Faizuloyeva; Karolina Olechowska (Financial Internet Quarterly, 2021)
This study analyses theoretical aspects of bankruptcy and financial analysis. Analysis of bankruptcy diagnostics is the most important condition for successful company management since the results of economic activity depend on the availability and efficiency of the use of financial resources. The study of the institution of bankruptcy is essential for high-quality business conduct. Thus, as a practical part this study implemented analyses of financial condition and bankruptcy likelihood in aviation on the example of one of the biggest airlines - PJSC Aeroflot. Research resulted in findings confirming the instability of the company's financial condition and downward trend on the Z index related to decrease in demand, mostly due to the pandemic of COVID-19.
Keywords: G3; G33; L93; 330; financial analysis; aviation industry; bankruptcy